ETHICAL ASPECT OF SOCIAL DOCTRINE OF CHRISTIANITY - Іщук, Н. В. (Proceedings of the Kyiv Aviation Institute. Series: Philosophy. Cultural, 2016)
Here is elucidated the ethical discourse of social doctrine of the contemporary Christianity from the position of the most fundamental dogmas. The spiritual premises and personality’s aspects of Christian communal celebration of the world have been revealed.